How to do things with speeches: a critical discourse analysis of military coup texts in Nigeria - Bello, Umar (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2020)
Coup speeches that usher the military into political power in Nigeria are the central focus of this thesis. There are seven coup speeches that are notable in the changing of the political course in Nigeria and in enabling the military to rule Nigeria for 30 years, establishing another alternative political construct and party (Bangura 1991). The seven coup speeches along with two others, one a colonial proclamation of conquest and the other a counter coup speech (altogether making nine) constitute the data of this thesis. The analysis done here uses Critical Discourse Analysis, based on a combination of Fairclough (1989, 2001), Fairclough and Fairclough (2012), Thompson's (1984, 1988 and 1990) works with complementary insights by Chilton (2004), to analyze the speeches in order to understand the ideologies, perceptions and arguments of the coup makers enshrined in the texts. I also employ a concordance analytic system in corpus linguistics to sort uses of important terms and lexical items. The analysis is divided into three broad parts, namely: an analysis of representation of social actors and their action, an analysis of the processes of interpellation and then an analysis of the premises of the arguments contained in the speeches. In the concluding part, there is a discussion of the dialectical nature of the coup speeches especially in the areas of mutual influences which aids in the gradual sedimentation of the political ideology of the military. In particular, there is a longitudinal intertextual analysis across all the speeches, from the earliest to the latest, to see how a coup speech genre is created. The contribution of this work to knowledge is in terms of combining discourse analysis and social theory to illuminate some aspects of Nigeria's socio- political crises in depth and multifariously. This work helps in understanding the nature of Nigerian autocratic democracy, subservient followership by the citizenry and the supremacy of the military elite. The work employs a novel combination of representation, argumentation, interpellation and constitutive intertextuality in understanding military discourse. It looks at speaker intention, the exploitation of interpretation or reception and the formation of subjects in general and each with its importance and social context. The work as a whole reveals that the military try to build legitimacy by way of establishing authority through rhetorical arguments in varying degrees. These arguments are laid bare, and what they discern is that charges are decidedly trumped up by the military against their opponents and constructed to suit the spin of their moments. The coup makers in some instances construct strawmen of opponents and then go ahead to attack their constructed assumptions or they charge without substance using nominalizations, metaphorical constructions and presuppositions. They apply stipulative definitions and emotionally loaded words in evaluating their actions favourably and also in the negative evaluation of the actions of the opponents. At the level of interpellational analysis, the data reveals the use of language in gradually hailing the citizens as military subjects. The role of the audience changes here i.e. from those to be convinced in rhetorical evaluation of opponents to those to be firmly controlled. The persistent hailing and positioning of the citizens as military subjects help in concretizing their subjecthood. The reaction of the people in affirmation of support to the rule of the military is crucial and it completes the interpellation process. As observed by Clark (2007, 141) "many African societies are so inured to military intervention as not to regard it as aberrant" . This inuring of the societies has to do with hegemonic ideological practices in military discourses claiming legitimacy and the right to rule. At the reception level, this shows that most of the citizens have bought into the dominant ideology and are as such interpellated by it or have adopted what Hall (2015, 125) would call the 'dominant-hegemonic position'. Aspects of argumentation, speech acts, and deontic modals used by the coup makers help in gradually solidifying the subservient nature of the citizens to the military junta. The diachronic and intertextual nature of the analysis also reveals that the colonial proclamation of conquest in Nigeria by Lord Fredrick Lugard possibly influenced the first coup speech in 1966 in terms of structure and genre. There are traces of the colonial proclamations found in the 1966 coup speech. In substance, the military appear to copy their colonial progenitors. Historically, the military were formed as an army of colonial conquest. There is a dialectical interplay between colonial discourse and military coup speeches. The first coup speech, for its part, influences other coup speeches and they in general impact on civilian political language. The work analyzes from the minute to the global and in this bid unties the layers of assumptions, constructions and points of views that underpin an otherwise objective presentation of reality. The study also engages social theory in illuminating aspects of discourse, social practice and political action. The works of post-structuralists like Foucault, Althusser, Bourdieu, Habermas, Laclau and Mouffe, Derrida etc. are employed in shedding light on the processes of social formation in the interpellation of subjects and in the construction of a new political authority by the military regimes.
Keywords: Speeches, addresses, etc., Nigerian -- 20th century -- History and criticism; Critical discourse analysis -- Nigeria; Corpora (Linguistics); Social sciences -- Philosophy; Intertextuality; Interpellation -- Nigeria; Forensics (Public speaking); Oratory -- Nigeria; Nigeria -- Politics and government -- 1960-; Nigeria -- Social conditions -- 1960-